High-speed 2D light-sheet fluorescence microscopy enables quantification of spatially varying calcium dynamics in ventricular cardiomyocytes - Dvinskikh, Liuba; Sparks, Hugh; MacLeod, Kenneth T.; Dunsby, Chris (Frontiers in Physiology, 2023)
Reduced synchrony of calcium release and t-tubule structure organization in individual cardiomyocytes has been linked to loss of contractile strength and arrhythmia. Compared to confocal scanning techniques widely used for imaging calcium dynamics in cardiac muscle cells, light sheet fluorescence microscopy enables fast acquisition of a 2D plane in the sample with low phototoxicity. A custom light-sheet fluorescence microscope is used to achieve dual-channel 2D timelapse imaging of calcium and the sarcolemma, enabling calcium sparks and transients in left and right ventricle cardiomyocytes to be correlated with the cell microstructure. Imaging electrically stimulated dual-labelled cardiomyocytes immobilized with para nitroblebbistatin, a non-phototoxic, low fluorescence contraction uncoupler, with sub-micron resolution at 395 fps over a 38 µm × 170 µm FOV allowed characterization of calcium spark morphology and 2D mapping of the calcium transient time-to-half-maximum across the cell. Blinded analysis of the data revealed sparks with greater amplitude in left ventricle myocytes. The time for the calcium transient to reach half-maximum amplitude in the central part of the cell was found to be, on average, 2 ms shorter than at the cell ends. Sparks co-localized with t-tubules were found to have significantly longer duration, larger area and spark mass than those further away from t-tubules. The high spatiotemporal resolution of the microscope and automated image-analysis enabled detailed 2D mapping and quantification of calcium dynamics of n = 60 myocytes, with the findings demonstrating multi-level spatial variation of calcium dynamics across the cell, supporting the dependence of synchrony and characteristics of calcium release on the underlying t-tubule structure.